2012
DOI: 10.1186/2046-1682-5-11
|View full text |Cite
|
Sign up to set email alerts
|

Molecular dynamics and mutational analysis of the catalytic and translocation cycle of RNA polymerase

Abstract: BackgroundDuring elongation, multi-subunit RNA polymerases (RNAPs) cycle between phosphodiester bond formation and nucleic acid translocation. In the conformation associated with catalysis, the mobile “trigger loop” of the catalytic subunit closes on the nucleoside triphosphate (NTP) substrate. Closing of the trigger loop is expected to exclude water from the active site, and dehydration may contribute to catalysis and fidelity. In the absence of a NTP substrate in the active site, the trigger loop opens, whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
81
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(86 citation statements)
references
References 54 publications
5
81
0
Order By: Relevance
“…This Gly-Gly pair is referred to as a "hinge," and we found that it can transiently lose its α-helix secondary structure (Fig. S5C), consistent with previous MD simulation studies on a short timescale (21). We also examined if the BH bending is coupled with the clamp motion by computing its cross-correlation (Fig.…”
Section: Resultsmentioning
confidence: 63%
See 2 more Smart Citations
“…This Gly-Gly pair is referred to as a "hinge," and we found that it can transiently lose its α-helix secondary structure (Fig. S5C), consistent with previous MD simulation studies on a short timescale (21). We also examined if the BH bending is coupled with the clamp motion by computing its cross-correlation (Fig.…”
Section: Resultsmentioning
confidence: 63%
“…Our simulations of translocation events, together with previous simulations (9,(20)(21)(22), provide important mechanistic and kinetic insights of several key steps in Pol II transcription. Our previous simulation study has suggested that the PPi release is rapid [at ∼1 μs (9)].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In these conformations, during translocation, it is the BH that is seen to play a more prominent role [as it was originally proposed by Bar-Nahum et al (4)] and the TL, although unfolded in both cases, is thought to assist the BH in translocation. As a whole, structural studies indicate that transcription elongation most likely involves a concerted motion of the "BH/TL unit" (9,14,16,(19)(20)(21)(22).In addition, several bulk studies revealed that most TL mutations that alter RNAP's elongation rate affect its pausing behavior too (4,8,10), suggesting that the TL is also involved in polymerase pause regulation. Furthermore, Toulokhonov et al (8) have shown that in paused complexes the TL adopts a conformation that inhibits nucleotide addition, but which also blocks binding of the transcription inhibitor streptolydigin (known to bind the unfolded TL).…”
mentioning
confidence: 99%
“…In these conformations, during translocation, it is the BH that is seen to play a more prominent role [as it was originally proposed by Bar-Nahum et al (4)] and the TL, although unfolded in both cases, is thought to assist the BH in translocation. As a whole, structural studies indicate that transcription elongation most likely involves a concerted motion of the "BH/TL unit" (9,14,16,(19)(20)(21)(22).…”
mentioning
confidence: 99%